PENGARUH KUALITAS JASA DAN KEPUASAN PELANGAN PADA NIAT PEMAKAIAN ULANG JASA BENGKEL HONDA - I Made Surya Prayoga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
Repurchase intention is a post-purchase action caused by the satisfaction received by the customer for the product consumed previously. If the product meets customer expectations, the customer will buy or reuse the product. The better the quality of service, the customer will be satisfied, but the quality of service for customers is expected, the customer will be dissatisfied and reluctant to reuse the service.The sample in this study was 157 customers of Honda Workshop, PT. Asaparis (Kita Motor) AHASS 0718 who have used services at this workshop. Data collection was carried out through a questionnaire method which was then processed using AMOS 16 software with Structural Equation Modeling (SEM) analysis technique.The analysis shows that service quality has a significant effect on customer satisfaction, customer satisfaction influences the significance of successful repurchase intention, and the quality of service has a significant importance on repurchase intention. Managerial implications that can be applied Honda Workshop, PT. Asaparis (Kita Motor) AHASS 0718 always guarantees and improves the quality of its services, in order to retain its customers, and encourage supporters who continue to improve to face competition.